Management of mine acid drainage in a constructed wetland using hyacinth plant and addition of organic materials - Fitri Arum Sekarjannah; S Setyo Wardoyo; Yanisworo Wijaya Ratih (Journal of Degraded and Mining Lands Management, 2019)
Coal mining is an activity to exploit land to get coal stored underground. Environmental problems in coal mining activities are generally associated with Acid Mine Drainage (AMD). The purpose of this study was to find out the best combination of organic matter and incubation time in remediating acid mine drainage on wetlands with water hyacinth plants. This research was conducted at PT Berau Coal in Tanjung Redeb, Berau, East Kalimantan. This study used a split-plot design. The main plot was the treatment of a combination of organic matter which consisted of 4 levels: A0 as a control (without organic matter), A1 with a combination of compost + sawdust (1:2), A2 with a combination of compost + sawdust (1:1), A3 with a combination of compost + sawdust (2:1). The subplot was treatment incubation time consisting of 2 levels, namely for 15 days and 33 days. Data analysis used variance analysis at the 5% level followed by the Duncan Multiple Range Test with a level of 5% when there were significant differences. The results showed that the addition of organic matter had a significant effect on the increase in pH and a decrease in the concentration of Mn in water, but it did not significantly affect the decrease in Fe concentration in water. The best combination of organic matter in acid mine remediation in this study was compost + sawdust (2:1) during the incubation time of 33 days